GEODYNAMIC FORMATION REGIME OF ROCKS OF THE UDOKAN COMPLEX - Abramov B.N. (My University, 2004)
The similarity of the Early Proterozoic Udokan sedimentary basin to complexes of passive continental margins was established during analysis of the geodynamic environments of the southern framework of the Siberian Craton. The objective of this work is to show that the lower complex formed under conditions of an active continental margin that is of importance for paleogeodynamic reconstructions.